Efeitos do etanol sobre a mucosa e osso palatinos do rato durante a lactação: estudo histopatológico e histométrico experimental - Kassis, Elias Naim (2011)
The ingestion of alcohol by a mother during lactation changes the composition of the milk, resulting in the origin of ethanol and acetaldehyde in the milk, and turns more severe the effects of the ethanol in infant rats. Objective: This work aimed to study the effects of ethanol at the palatine bone and palatine epithelium of young infants in 21 days of postnatal life, administered to the experimental rats during lactation. Materials and Methods: The experimental rats received ethanol at 20% in the drinking fountain ad libitum during those 21 day of nursing. Another group of animals received an amount of water similar to that group without ethanol. The infant rats were put to death with an extra dose of anesthesia in their 21 days of life. Their heads were separated from their body, put in 85mls of a 80% alcohol solution, 10 ml of formalin and 5ml of acetic acid, the palate area was cut in serial sections by frontal plans, in the same level were the molar are located, the cuts were about 6 micrometers and were treated with hematoxylin-eosin. The nuclear parameters of the palate epithelium, the cytoplasmatic volume and cellular, the relation nucleon/cytoplasm, numerical density and superficial, the thickness of the epithelium were all estimate. The average body weight of the infant rats in the ethanol group was 20,20 g and the other group average weight was 34,86gr. Histologically, the palate epithelium was thinner and it had more numbers of smaller cells with a bigger nucleon. The palate bone had more delicate and less trabeculo calcificated, and smaller osteocyte. Conclusion: In this experiment, the ethanol induced a epithelial hypotrophy condition and palate bone more delicate and less calcificated, showing a direct affect in the cells and trabeculo palate and also the poor development of the intoxicated infant rats.